Criminal justice system and confidence: immigrants settled in Málaga - Casado Patricio, Elena (My University, 2019)
The aim of the present investigation is to find out the level of confidence that the settled foreigners in Málaga have of the police and judicial systems, as well as determining if the level of confidence varies according to different social variables. According to the procedural justice theory, it is important to have an understanding of it since this confidence could have an influence in the cooperation within the institutions analyzed. Also, this investigation tries to demonstrate if confidence could be influenced by direct contact with these institutions as victims or victimizers. The methodology used was the structured questionnaire, to later analyze the data with the statistical program SPSS, specifically the non-parametric test was used and bivariate analysis to learn how variables were related. In this way, the results establish a different level of confidence depending on the institution analyzed, and the less confidence with a specific institution after being in contact with them.
Keywords: Inmigrantes - Málaga; Administración de justicia; Criminal justice system; Immigrants; Confidence